Aliran Filsafat Esensialisme dalam Pandangan Pendidikan Islam - Khurun In kamila; Nur Mafaza Karima; Nabiila Tsuroyya Azzahra; M Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Essentialism is a school that believes that the values contained in education should prioritize returning to values and culture that have been tested by time, which in turn will emphasize teaching that is clear and relevant to people's lives. The teaching method in essentialism is more traditional, where teachers play an important role in the teaching and learning process, while students are expected to receive and absorb the knowledge provided. In this article the author analyzes various sources, including books and journals, to discuss the view of essentialism in the context of developing a quality Islamic religious education philosophy. Essentialism emphasizes the importance of the core knowledge and values that must be taught to the younger generation. In the philosophy of Islamic religious education, this approach focuses on teaching fundamental teachings such as faith, morals and worship, which form the basis of students' character and spirituality. Thus, this article aims to provide knowledge about the importance of an essentialist approach in creating religious education that is not only of high quality, but also relevant to the needs of the times.